On internal trapped wave solutions with no-slip wall conditions - Smirnov, Sergey Viktorovich (Computational Continuum Mechanics, 2008)
Internal trapped wave solutions of a linearized set of hydrostatic ocean dynamics equations are considered in a semi-infinite,f-plane model basin of constant depth bordering a straight vertical coast. No-slip wall and free-slip bottom boundary conditions are assumed. Trapped wave solutions are presented for some reference values of the model parameters. When the wave length is shorter then Rossby deformation radius, the main features of the wave solutions are as follows: the Kelvin wave exponential offshore decay length decreases considerably with the wave length, an additional wave solution propagating in the opposite direction appears.